Nurses' Perception of Career Development and Organizational Commitment and Its Components in Private Hospitals in Indonesia - Theodorius Amelwatin (Eduvest - Journal of Universal Studies, 2026)
Career development and organizational commitment are critical factors in improving nurses’ performance and retention in private hospitals. However, understanding how nurses perceive career growth and its influence on their commitment remains essential, particularly in the Indonesian healthcare context where workforce stability is a key concern. This study aims to explore nurses’ perceptions of career development and organizational commitment, as well as to examine how demographic factors influence these relationships in private hospitals in Indonesia. The study employs a mixed-method approach with an explanatory sequential design. It begins with quantitative analysis identifying career growth and demographic factors (age, gender, work experience, and work location) as predictors of organizational commitment. This is followed by a qualitative phase using virtual focus group discussions (FGDs) with 30 purposively selected nurses from private hospitals in North Sulawesi. Data were collected through semi-structured interviews and analyzed using Reflexive Thematic Analysis. The findings reveal three main themes: a positive work environment, emotional involvement at work, and challenges faced in the hospital. These results confirm that career development significantly influences nurses’ organizational commitment, supported by both quantitative and qualitative evidence. Career development plays a vital role in strengthening nurses’ commitment to their organizations. Hospitals are recommended to design structured career development and counseling programs to enhance employee engagement and long-term retention.